Nutritional and Performance Considerations in the Master Athlete. Issue 1 (January 2016) - Hoogenboom, Barbara J.; McDaniel, Jessica; Krikke, Alyssa
Abstract : The masters athlete is a unique example of an individual who is meeting the challenges of aging by successfully maintaining an active and healthy lifestyle. Participation in sports and recreational activities throughout a lifetime takes dedication and commitment to all of facets of health that support such a lifestyle. For the purpose of this commentary, the masters athlete will be defined as those aged 50 years or older, consistent with the requirement for participation in the National Senior Games. Benefits of activity while aging, and the impact of proper nutrition and hydration on healthy functional aging will be discussed.